Physical and mental health outcomes of COVID-19 induced delay in oncological care: A systematic review - van Vliet, Ella D.; Eijkelboom, Anouk H.; van Giessen, Anoukh; Siesling, Sabine; de Wit, G. Ardine (Frontiers in Oncology, 2023)
Background. During the COVID-19 pandemic cancer patients might have experienced delays in screening, diagnosis and/or treatment. A systematic review was conducted to give an overview of the effects of COVID-19 induced delays in oncological care on the physical and mental health outcomes of cancer patients. Methods. MEDLINE and EMBASE databases were searched for articles on the effects of COVID-19 induced delays on physical and mental health outcomes. Results. Out of 1333 papers, eighteen observational, and twelve modelling studies were included. In approximately half of the studies, tumor stage distribution differed during the pandemic compared to before the pandemic. Modelling studies predicted that the estimated increase in the number of deaths ranged from 0.4 to 30%, and the estimated reduction in survival ranged from 0.02 to 35%. Varying results on the impact on mental health, e.g. anxiety and depression, were seen. Conclusions. Due to large methodological discrepancies between the studies and the varying results, the effect of COVID-19 induced delays on the physical and mental health outcomes of cancer patients remain uncertain. While modelling studies estimated an increase in mortality, observational studies suggest that mortality might not increase to a large extent. More longitudinal observational data from the pandemic period is needed for more conclusive results.